Answer:
x-intercept =
![(13)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/buz5wwjnygn21des9m463p0scn4nhv335s.png)
y-intercept =
![-13](https://img.qammunity.org/2020/formulas/mathematics/middle-school/e0unc0opecl3pcimnr3nh5e9covhk735j3.png)
Explanation:
We are given the following equation of a line and we are to find the x and y intercepts for it:
![y + 1 = 3 ( x - 4 )](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d4sijnjsepgzjdxhn0b7pr2ecf7h276vx1.png)
In order to find the x-intercept, we will substitute 0 in place of y to get:
![0 + 1 = 3 ( x - 4 ) \\\\ 1 = 3 x - 12 \\\\ 3 x = 1 + 12 \\\\ x = \frac { 13 } { 3 }](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wme05ltrfb1ijx9enf3cqs2xg9c9teoe50.png)
And to find the y-intercept, we need to substitute 0 in place of x:
![y + 1 = 3 ( 0 - 4 ) \\\\ y + 1 = -124 \\\\ y = - 12 - 1 \\\\ y = - 13](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zfy17w970rj68o58awf1934l6sifo5wtpn.png)
So the x-intercept is
while the y-intercept is
.